MELALUI STIMULASI MINAT BACA DAPAT MENINGKATKAN KOMPETENSI DAN KINERJA GURU DALAM MENGAJAR DI MADRASAH TSANAWIYAH NEGERI 1 LANGKAT - Ojar Ojar (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
The results of the school action research conducted by the author indicate that the value acquisition has increased very well, where the results of this study use quantitative data analysis with 10 respondents as the sample, while data management uses the product moment formula and t test. This can be seen from the correlation of the results of the calculation of the first cycle to the second cycle of Teacher Competence of 0.838 (categorized as very valid) with a t test value of 7.942 (categorized as very significant). And the correlation of the calculation results of the first cycle to the second cycle of Teacher Performance is 0.859 (categorized as very valid) with a t-test value of 9.315 (categorized as very significant). While all arithmetic results are greater than the table results, r table is 0.317 and t table is 0.727.Keywords: Reading Interest Stimulation, Competence, Teacher Performance